Memory and body of a resistant childhood: an analysis of Kamchaka, O ano em que meus pais saíram de férias and Infância clandestina - Siciliano, Tatiana; Helich, Tatiana; Moratelli, Valmir (Pontifícia Universidade Católica de São Paulo, 2023)
From the analysis of the films The Year My Parents Went on Vacation, by Cao Hamburguer (2006); Kamchatka, by Marcelo Piñeyro (2002), and Infância Clandestina, by Benjamin Ávila (2011), the Brazilian military dictatorial context in 1970 and the Argentinean context in 1976 and 1979 will be discussed, having as theoretical basis the discussion of the rescue of memory as a means to construction of identity, based on authors such as Jeanne Marie Gagnebin (2014), Beatriz Sarlo (2012) and Márcio Selligman-Silva (2003). The films express the trauma experienced in both countries from the playful perspective of the children of militants whose parents went underground. The framing brings to the foreground the marks experienced in the child's body, which, when narrated, suture the memories of a past marked by the practice of torture. Com base na análise dos filmes O ano em que meus pais saíram de férias (2006), de Cao Hamburger; Kamchatka (2002), de Marcelo Piñeyro; e Infância clandestina (2011), de Benjamin Ávila, este artigo aborda o contexto ditatorial militar brasileiro em 1970 e o argentino em 1976 e 1979, tendo como aportes teóricos autores como Jeanne Marie Gagnebin (2014), Beatriz Sarlo (2012) e Márcio Selligman-Silva (2003) na discussão da memória como meio para construção de identidade. Os filmes expressam o trauma vivido nos dois países sob a perspectiva lúdica infantil dos filhos de militantes, cujos pais caíram na clandestinidade. O enquadramento traz para primeiro plano as consequências no corpo infantil que, ao serem narradas, suturam as lembranças de um passado marcado pela violência.